2021
DOI: 10.3390/biomedicines9111729
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-Based Immunotoxins for Colorectal Cancer Therapy

Abstract: Monoclonal antibodies (mAbs) are included among the treatment options for advanced colorectal cancer (CRC). However, while these mAbs effectively target cancer cells, they may have limited clinical activity. A strategy to improve their therapeutic potential is arming them with a toxic payload. Immunotoxins (ITX) combining the cell-killing ability of a toxin with the specificity of a mAb constitute a promising strategy for CRC therapy. However, several important challenges in optimizing ITX remain, including su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 182 publications
(202 reference statements)
0
16
0
Order By: Relevance
“…However, systemic treatment of tumors would require improving the directionality of the molecule. This can be achieved by the conjugation of an antibody or antibody fragment directed against a tumor molecule with GRNLY, generating a so-called fourth-generation immunotoxin [ 16 ]. Our team designed three immunotoxins that conjugated GRNLY with scFv, one directed against CEA (Carcino-embryonic antigen) [ 21 ], and two against the Tn antigen [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, systemic treatment of tumors would require improving the directionality of the molecule. This can be achieved by the conjugation of an antibody or antibody fragment directed against a tumor molecule with GRNLY, generating a so-called fourth-generation immunotoxin [ 16 ]. Our team designed three immunotoxins that conjugated GRNLY with scFv, one directed against CEA (Carcino-embryonic antigen) [ 21 ], and two against the Tn antigen [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the immunotoxin moxetumomab pasudotox, an anti-CD22 scFv fused with the Pseudomonas Exotoxin A PE38 has been approved for the treatment of hairy cell leukaemia [ 15 ]. Another PE38-based immunotoxin, oportuzumab monatox, which includes an scFv directed against EpCAM was in review as of August 2021 for bladder cancer treatment [ 16 ]. On the othe hand, our research group has studied the antitumor capacity of recombinant 9 kDa granulysin (GRNLY) for more than two decades [ 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Two review articles exploited the possibility of application of immunoconjugates (IC) for the therapy of colorectal cancer [ 14 ] and sarcoma [ 15 ].…”
mentioning
confidence: 99%
“…Several monoclonal antibodies (mAbs) are included among the treatment options for advanced CRC, but often they may have limited clinical activity. The review article by Sanz et al [ 14 ], reported data about the wide variety of ICs tested in preclinical studies and clinical trials for CRC treatment. For each conjugate, the target, the carrier and payload are described in detail and the preclinical efficacies in vitro and in vivo are reported.…”
mentioning
confidence: 99%